THE MODERN MARKET CENTER AT PASAR MINGGU JAKARTA AS AN ART SPACE USING TOD SUPPORT - Muhammad Rifqie Izzulhaq; Yuke Ardhiati (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: The purpose of this research is to design a public facility which was originally a traditional market with daily commodities to become a modern market with an expanded role as an art market (art space). Research methods: The design method used in the design starts from the stage of finding design ideas, containing ideas and problems that can potentially arise in the design. This stage aims to create ideas based on theory. This data collection includes literature studies and previous studies. Findings: The result of this design is a building that can be oriented to the economy and the arts so that it can accommodate human needs physically and spiritually. The application of the market concept and art space has made the market, which was previously known as a place that was only used to sell daily commodities, which can be used by the community for gathering and other natural organic activities such as art. Implications: To combine the market and the Art Space, a communal place is made, namely a plaza that is useful as a shelter for humans so that the market can also become a more lively place.